Menakar Argumentasi MENAKAR ARGUMENTASI STATUS TAUQIFI-IJTIHADI DALAM PENAMAAN SURAT-SURAT AL-QUR’AN - M. Fatih (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2022)
The names of the surahs of the Qur'an have existed since the time of revelation, which function as identities and distinctions between the verses of one surah and the verses of other surahs. Among the letters there are those with one name, two names, three names and so on. Scholars have different opinions as to whether the names of the Surahs of the Qur'an are based on theinstructions of the Prophet SAW. (tauqifi) or the results of the ijtihad of the companions (ijtihadi). Many scholars are of the opinion that the names of the surahs of the Qur'an are tauqifi even though they are not uniform in setting the terms. Some scholars are of the opinion that the naming of the letters of the Qur'an is the ijtihad of the companions. They require tauqifian the name of the letter with a hadith history that explicitly mentions the name of each letter. In this case, their value will not be fulfilled. Each group competes with each other arguments and reason to strengthen their arguments. This contradiction gives rise to a third opinion which says that some of the names of the letters are tauqifi, and others are ijtihadi. Efforts to this third opinion have not satisfied each party. Then came the idea of rationalization with the view that the names of the letters made by the companions were the result of what they heard and memorized from the Prophet SAW., or these names were the popular names of a famous letter at the time of the Prophet, he knew and did not know. deny this, so that it can be seen as the basis of justification of the Prophet (taqriri).